HLA-DRB111 and variants of the MHC class II locus are strong risk factors for systemic juvenile idiopathic arthritis - Ombrello, Michael J.; Remmers, Elaine F.; Tachmazidou, Ioanna; Grom, Alexei; Foell, Dirk; Haas, Johannes-Peter; Martini, Alberto; Gattorno, Marco; Özen, Seza; Prahalad, Sampath; Zeft, Andrew S.; Bohnsack, John F.; et al. (Proceedings of the National Academy of Sciences - PNAS, 2015)
To determine whether genetic variation within the MHC locus influences the risk of developing systemic juvenile idiopathic arthritis (sJIA), we examined a dense set of MHC region single nucleotide polymorphisms, classic HLA alleles, and the individual amino acids of HLA molecules in nine independent sJIA case-control populations. Association testing revealed that genetic variants within the MHC class II gene cluster significantly influenced sJIA risk in every study population. The strongest risk factor for sJIA was HLA-DRB1*11 , which conferred at least a two-fold increase in disease risk in each population studied. These data implicate the interaction of antigen presenting cells with T cells in the pathogenesis of sJIA. Systemic juvenile idiopathic arthritis (sJIA) is an often severe, potentially life-threatening childhood inflammatory disease, the pathophysiology of which is poorly understood. To determine whether genetic variation within the MHC locus on chromosome 6 influences sJIA susceptibility, we performed an association study of 982 children with sJIA and 8,010 healthy control subjects from nine countries. Using meta-analysis of directly observed and imputed SNP genotypes and imputed classic HLA types, we identified the MHC locus as a bona fide susceptibility locus with effects on sJIA risk that transcended geographically defined strata. The strongest sJIA-associated SNP, rs151043342 [ P = 2.8 × 10 −17 , odds ratio (OR) 2.6 (2.1, 3.3)], was part of a cluster of 482 sJIA-associated SNPs that spanned a 400-kb region and included the class II HLA region. Conditional analysis controlling for the effect of rs151043342 found that rs12722051 independently influenced sJIA risk [ P = 1.0 × 10 −5 , OR 0.7 (0.6, 0.8)]. Meta-analysis of imputed classic HLA-type associations in six study populations of Western European ancestry revealed that HLA-DRB1*11 and its defining amino acid residue, glutamate 58, were strongly associated with sJIA [ P = 2.7 × 10 −16 , OR 2.3 (1.9, 2.8)], as was the HLA-DRB1*11—HLA-DQA1*05—HLA-DQB1*03 haplotype [6.4 × 10 −17 , OR 2.3 (1.9, 2.9)]. By examining the MHC locus in the largest collection of sJIA patients assembled to date, this study solidifies the relationship between the class II HLA region and sJIA, implicating adaptive immune molecules in the pathogenesis of sJIA.